Rice kernel morphometrics: Exploring the physical dimensions of indigenous traditional landrace diversity through physio metric studies - S. Manju Devi1, M. Raveendran2, R. Pushpam3, S.Muthuramu4, R. Pushpa5, N. Sritharan6, R. Suresh6 and A. John Joel1* (Electronic Journal of Plant Breeding)
Development and widespread adoption of modern rice varieties has led bottlenecking of many beneficial alleles and there is a significant decline in the cultivation of traditional landraces, which results in substantial loss of genetic diversity. The varied consumer preference in terms of eating habit and other preparations in rice sustains the diversity in the grains. Hence, present day market trend in rice revolves around the choice of consumers which are mainly based on the physical characteristics of rice. To categorize rice based on kernel characteristics, in this study, a total of 500 rice genotypes were taken for assessing the physical properties of kernel viz., seed length, seed width, length/width ratio, seed thickness, bulk density, geometric mean diameter, sphericity, aspect ratio and hundred seed weight. All the traits exhibited ample amount of significant variations (P<0.05). High GCV was exhibited by bulk density and high heritability was observed by hundred seed weight, seed thickness, bulk density and seed width indicating that these traits were highly influenced by genetic factor and less influence of environment. Among these traits, hundred seed weight, seed thickness, bulk density and seed width exhibited high heritability coupled with high genetic advance as per cent of mean indicating the additive gene action and amenable for selection. Principal component analysis observed that the f irst three principle components explained most of the total variations present in the studied genotypes. Specifically, the first principal component (PC1) contributed the most, representing 35.24% of the variability followed by PC2 and PC3. In view of size and shape, most rice genotypes exhibited kernels that were predominantly short and narrow, succeeded by those that were short and of medium width. To categorise the seed diversity among the kernels of landraces, Mahalanobis D2 statistics analysis was performed. Based on this the 500 rice landraces were grouped into five distinct clusters. Among the clusters, the Cluster II predominantly comprised kernels of medium and short lengths, medium widths. In contrast, Cluster V predominantly featured grains of very short lengths, narrow to very narrow widths. From the five clusters, four genotypes per cluster emphasising high mean value for bold and slender shape were selected for observation of cooking quality traits. During cooking, grain expands in all the dimensions but usually more in length. The gelatinization temperature based on alkali digestion values showed that 16 rice genotypes had low alkali spreading values, leading to stickier rice. Meanwhile, four genotypes exhibited intermediate alkali spreading values, which are preferred for parboiling. Therefore, an understanding on the kernel architecture and grouping them based on the physical dimensions like seed thickness, seed width, and bulk density, as well as kernel colour along with hundred seed weight will be useful in formulating breeding programme for kernel traits or consumer preferences. This selection aimed to align breeding goals with market needs, guaranteeing economic feasibility and sustainability in rice farming.